Unregistered Intermarriage in the Morosi Mining Area: Between Adat Law and State Regulation - Yuningsih, Deity; Alwi, Idaman; Wa Ode Zuliarti; Saraswati, Saraswati; Muh. Saleh Saputra, La Ode (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2026)
This study aims to examine the phenomenon of unregistered intermarriage between local communities and foreign workers in mining areas and to analyze the interaction between customary law and formal legal regulations. The research employs a qualitative approach through in-depth interviews with mixed-marriage couples, community leaders, and local government officials. The collected data were analyzed to identify the challenges and opportunities associated with the legalization of marriage. The findings indicate that many couples opt for unregistered marriages due to limited access to official civil registration services and the strong influence of customary norms. The novelty of this research lies in the development of a digital-based solution to support the registration of mixed marriages, consisting of an online registration platform and a legal education application. This solution is designed to bridge the gap between customary law and formal legal frameworks while improving access to legal marriage registration for couples in mining regions. Consequently, this study not only contributes to a deeper understanding of the social and legal complexities surrounding unregistered intermarriage but also offers an innovative digital approach to enhance legal certainty and the protection of couples’ rights in the context of mixed marriages